PENERAPAN E-LEARNING DI PERGURUAN TINGGI - Santi Maudiarti (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2018)
This research was aimed to describe the application of e-learning at the Department of Educational Technology, Faculty of Education Science, Jakarta State University. This research used case study research method with multiple data collection. Research findings revealed that (1) there are 20 courses conducted using e-learning by 7 lecturers; (2) blended learning was used; (3) e-learning itself developed through analysis, design and development phases; (4) analysis phase including students characteristics analysis, e-elarning environment analysis and content analysis; (5) design phase including online leaerning design (designing content, discussion for online discussion forum, assignment for online assignment, and test item for online evaluation) and face-to-face learning design including deep discussion, case study, and demonstration and practices; (6) student acceptance on blended was high; (7) there were several barriers in implementing e-learning due to lack of policy and ICT infrastructure support; and (8) supporting factors of implementation e-learning were the high commitment from lecturers and students, and the familiarity of students toward ICT. Based on research findings, Department of Educational Technology was recommended to have a minimum standard of development and implementation of e-learning and to enhance ICT infrastructure support, esp. access adequate internet connectivity. References Chaeruman, U.A. (2008). Penerapan blended learning. Diakses melalui http://www.teknologipendidikan.net/2008/11/27/contoh-penerapan-blended-learning/ Clark, R.C. & Meyer, R.E. (2003). E-learning strategies: Design, delivery, implementation and evaluation. San Francisco: John Wiley & Sons, Inc. Dabbagh, N. & Bannan-Ritland, B. (2005). Online learning: Concept, strategies, and application. New Jersey: Pearson education, Inc. Gredler, M.E. (2011). Learning and instruction: Teori dan aplikasi. Terjemahan Tri Wibowo B.S. edisi keenam. Jakarta: Kencana Prenada Media Group. Holmes, B. & Gardner, J. (2006). E-learning concepts and practice. London: SAGE Publication, Ltd. Khan, B. (2005). Managing e-learning strategies: Design, delivery, implementation, and evaluation. USA: Idea Group, Inc. Miarso,Y. (2005). Menyemai benih teknologi pendidikan. Jakarta: Kencana. Morrison, G.R., Ross, S.M., & Kemp, J.E. (2007). Designing effective instruction. USA: John Wiley&Sons, Inc. Prawiradilaga, D.S. (2007). Prinsip desain pembelajaran. Jakarta: Kencana Prenada Media Group. Prawiradilaga, D.S & Siregar, E. (2004). Mozaik teknologi pendidikan. Jakarta: Kencana. Siregar, E., & Nara, H. (2010). Teori belajar dan pembelajaran. Ciawi, Bogor: Ghalia Indonesia. Wahono, R.S. (2008). Meluruskan salah kaprah tentang e-learning. Diakses melalui http://romisatriawahono.net/2008/01/23/meluruskan-salahkaprah-tentang-e-learning/ Yin, R.K. (2008). Studi kasus: Desain dan metode. Jakarta: PT. Grafindo Persada.